Mapping of bibliometric studies in healthcare: evidence from South Asian countries - Ali, Javed; Airij, Awais Gul; Malik, Najeeb Ur Rehman (Universiti Kebangsaan Malaysia, 2025)
The current bibliometric study is designed to analyse the bibliometric studies in healthcare specific to South Asian countries. Bibliometric and thematic analysis was performed on 85 screened documents and author keywords respectively from Scopus. The current study covered the timespan from 2013 to 2023. Results are classified into three broad themes i.e., bibliometric, healthcare, and technological mapping. These three themes are grouped with the relevant sub-themes. Findings reveal the publication output trend, prominent authors, subject areas, journals, and affiliated institutions. Important and conspicuous words (author keywords) are visualized in bibliometric maps showing the noticeable themes for future research directions such as machine learning, blockchain, deep learning, and scientometrics in the area of healthcare. This study guides the researchers who are involved in conducting bibliometric studies specifically in healthcare. It serves as a compilation of published bibliometric studies through which different uncovered and underexplored aspects of healthcare research have emerged.